Allison Bain; Or, By a Way She Knew Not - Robertson, Margaret M. (Margaret Murray), 1821-1897; Edwards, G. H. (George Henry) (Salt Lake City, UT : Project Gutenberg, 2008)
"Allison Bain; Or, By a Way She Knew Not" by Margaret M. Robertson is a psychological novel written in the late 19th century. The book revolves around the life of Allison Bain, who is grappling with loss, obligation, and the harsh realities of her circumstances, particularly following the death of her father and the troubled fate of her brother. The narrative dives deep into themes of suffering, resilience, and societal expectations as Allison navigates a world tainted by sorrow and hardship. The opening of the novel introduces Mr. Hadden, Allison's minister, who is concerned for Allison on the day of her father's burial. Accompanied by his son Alexander, he is determined to visit the distraught Allison, reflecting on her struggles and the oppressive atmosphere of the community surrounding her. The dialogue reveals the troubled history of Allison$1 (Bs marriage and her family's plight, particularly her brother's wrongful imprisonment and their mother$1 (Bs illness, creating a palpable tension surrounding Allison's current challenges. As the minister expresses hope alongside his fears for Allison's future, readers are drawn into a world where personal pain intertwines with communal life, setting the stage for an exploration of redemption and the human condition. (This is an automatically generated summary.)s
Release date is 2008-03-30
Produced by Nick Hodson of London, England
Keywords: Canadian fiction